Echocardiographic Findings Predict In-Hospital and 1-Year Mortality in Left-Sided Native Valve Staphylococcus aureus Endocarditis. (July 2015) - Lauridsen, Trine K.; Park, Lawrence; Tong, Steven Y.C.; Selton-Suty, Christine; Peterson, Gail; Cecchi, Enrico; Afonso, Luis; Habib, Gilbert; Paré, Carlos; Tamin, Syahidah; Dickerman, Stuart; Bayer, Arnold S.; et al.
<x xml:space="preserve">Abstract</x> Background— Staphylococcus aureus left-sided native valve infective endocarditis (LNVIE) has higher complication and mortality rates compared with endocarditis from other pathogens. Whether echocardiographic variables can predict prognosis in S aureus LNVIE is unknown. Methods and Results— Consecutive patients with LNVIE, enrolled between January 2000 and September 2006, in the International Collaboration on Endocarditis were identified. Subjects without S aureus IE were matched to those with S aureus IE by the propensity of having S aureus. Survival differences were determined using log-rank significance tests. Independent echocardiographic predictors of mortality were identified using Cox-proportional hazards models that included inverse probability of treatment weighting and surgery as a time-dependent covariate. Of 727 subjects with LNVIE and 1-year follow-up, 202 had S aureus IE. One-year survival rates were significantly lower for patients with S aureus IE overall (57% S aureus IE versus 80% non-S aureus IE; P<0.001) and in the propensity-matched cohort (59% S aureus IE versus 68% non-S aureus IE; P<0.05). Intracardiac abscess (hazard ratio, 2.93; 95% confidence interval, 1.52–5.40; P<0.001) and left ventricular ejection fraction <40% (odds ratio, 3.01; 95% confidence interval, 1.35–6.04; P=0.004) were the only independent echocardiographic predictors of in-hospital mortality in S aureus LNVIE. Valve perforation (hazard ratio, 2.16; 95% confidence interval, 1.21–3.68; P=0.006) and intracardiac abscess (hazard ratio, 2.25; 95% confidence interval, 1.26–3.78; P=0.004) were the only independent predictors of 1-year mortality. Conclusions— S aureus is an independent predictor of 1-year mortality in subjects with LNVIE. In S aureus LNVIE, intracardiac abscess and left ventricular ejection fraction <40% independently predicted in-hospital mortality and intracardiac abscess and valve perforation independently predicted 1-year mortality.